Hypoglycemia in Pregnant Women with Type 1 Diabetes: Is It Inevitable? - Rosenn, Barak M.; Khoury, Jane C.; Mimouni, Francis; Ehrlich, Shelley; Miodovnik, Menachem (American Journal of Perinatology, 2024)
The human body has abundant mechanisms to counteract hypoglycemia and prevent neuroglycopenia primarily involving the secretion of glucagon and adrenalin. Within several years from the onset of diabetes, people with type 1 diabetes lose their ability to mount a counterregulatory response to hypoglycemia and develop hypoglycemia unawareness, thus being at risk for deteriorating to a state of severe hypoglycemia and neuroglycopenia. Pregnant individuals with type 1 diabetes are particularly prone to experience severe hypoglycemia during the first half of pregnancy. This may be not only due to the institution of strict glycemic control and the nausea and vomiting prevalent during the early months of pregnancy, but also because the counterregulatory responses are further diminished during pregnancy. Severe hypoglycemia during early pregnancy does not appear to increase the risks of spontaneous abortion or congenital fetal malformations, but the potential long-term effects on the fetus are unknown. Recent technological advances have contributed to improved glycemic control and time in range as well as decreased risk of hypoglycemia in people with diabetes. These advances include treatment with insulin analogs, use of continuous glucose monitors, and closed-loop systems for administration of insulin. Limited studies have demonstrated that pregnant individuals with type 1 diabetes may also benefit from these modalities. While ongoing research continues to explore the adjustment of closed-loop systems for optimal use during pregnancy, more effort is needed to explore the optimal use of these modalities in pregnancy.
Keywords: hypoglycemia; diabetes; type 1 diabetes; counterregulatory hormones